Union of the Comoros : 2008 Article IV Consultation and Request for Emergency Post-Conflict Assistance and for Disbursement Under the Rapid-Access Component of the Exogenous Shocks Facility-Staff Report; Staff Supplement; Staff Statement; Public Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Union of the Comoros. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses the Union of Comoros' 2008 Article IV Consultation and request for Emergency Post-Conflict Assistance and disbursement under the Rapid-Access Component of the Exogenous Shocks Facility. Real GDP growth has been well below the regional average, and per-capita income has steadily declined. Rising food and energy costs have worsened the external position, and the external debt burden is far above the Heavily Indebted Poor Countries threshold. To reverse the deteriorating trend, the authorities have initiated measures in 2008 to contain the fiscal deficit and begin to address macroeconomic and structural impediments to growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet